Improvement of levodopa induced dyskinesias by thalamic deep brain stimulation is related to slight variation in electrode placement: possible involvement of the centre median and parafascicularis complex. Issue 3 (1st September 1999) - Caparros-Lefebvre, Dominique; Blond, Serge; Feltin, Marie-Pierre; Pollak, Pierre; Benabid, Alim Louis
Abstract : OBJECTIVE: To define the reason why two teams using the same procedure and the same target for deep brain stimulation (DBS) obtained different results on levodopa induced dyskinesias, whereas in both, parkinsonian tremor was improved or totally suppressed. METHODS: Deep brain stimulation can replace lesions in the surgical treatment of abnormal movements. After 10 years of experience with DBS in Parkinson's disease, a comparison of results between the teams of Lille (A) and Grenoble (B) was carried out, for as long as they used intraoperative ventriculography. Both teams aimed at the same target, the ventralis intermedius nucleus of the thalamus (VIM), but team A found a clear improvement of choreic peak dose dyskinesias, whereas team B did not consistently. Therefore all teleradioanatomical data of both teams were re-examined and compared with the therapeutic effects. Location of 99 monopolar electrodes of thalamic stimulation applied to treat parkinsonian tremor has been retrospectively measured (team A included 21 patients, 22 electrodes; team B included 52 patients, 74 electrodes). Peak dose levodopa dyskinesias were suppressed by DBS in all nine patients of team A, four of which were severely disabling. Only eight out of 32 patients from team B experienced a moderate (four) or clear (four) improvement of dyskinesias, whereas in the remaining 24 patients, dyskinesias were unchanged with stimulation. RESULTS: The mean centre of team A's electrodes was on average 2.9 mm deeper, more posterior and medial than team B's ( t =8.05; p<0.0001). This does not correspond to the coordinates of the VIM, but seems to be closer to those of the centre median and parafascicularis complex (CM-Pf), according to stereotaxic atlases. Considering only the dyskinetic patients, significant differences were found in the electrode position according to the therapeutic effects on levodopa dyskinesias, but they were not related to the team membership. Improvement in levodopa dyskinesias was significantly associated with deeper and more medial placement of electrodes. CONCLUSION: The retrospective analysis of patients treated with DBS using comparable methodologies provides important information concerning electrode position and therapeutic outcome. The position of the electrode is related to the therapeutic effects of DBS. The results support the hypothesis that patients experiencing an improvement of dyskinesias under DBS are actually stimulated in a structure which is more posterior, more internal, and deeper than the VIM, very close to the CM-Pf. These results are consistent with neuroanatomical and neurophysiological data showing that the CM-Pf is included in the motor circuits of the basal ganglia system and receives an important input from the internal pallidum. This suggests that the CM-Pf could be involved specifically in the pathophysiology of levodopa peak dose dyskinesias.